Surveying Antioxidant Activity of Hydroalcoholic Extract of Matricaria chamomilla L. and Comparing it to Lovastatin in Rat - Amraei, Mansour (Asian Journal of Pharmaceutics (AJP), 2019)
Background: One of the most known reasons of the majority of diseases is oxidative stress, created by free radicals, and the most important defensive factors against these free radicals are antioxidants that can be naturally found in most herbs; hence, we studied antioxidant activity of Matricaria chamomilla L. hydroalcoholic extract (MCHAE) and compared it to lovastatin in Wistar rats. Materials and Methods: In this research, 30 Wistar rats (165 Â± 15 g) were used that were randomly put in the control group (common diet), sham group (high cholesterol diet [2%]), experimental Groups of 1 and 2 (high cholesterol diet 2%) and arrangement with 0.55 and 1.1 mg/ml doses of M. chamomilla L. extract), and experimental Group 3 (high cholesterol diet [2%] and 10 mg/kg lovastatin). At the beginning and end of the study, blood sampling was performed on the rats, and plasma serum malondialdehyde (MDA) and red blood cell (RBC) superoxide dismutase (SOD) concentrations were measured. The results were analyzed by SPSS 16 software and P < 0.05 was considered as the limit of statistical inference. Results: The amount of SOD in RBC and plasma MDA in control group did not show a significant difference. In addition, the levels of these two enzymes in experimental Groups of 1 and 3 that, respectively, received 0.55 mg/ml MCHAE and 10 mg/kg lovastatin drug did not show a significant difference at the beginning and end of the study and were in normal level, â€œin spite of receiving high cholesterol (2%) diet. But 1.1 mg/ml dose of hydroalcoholic extract of Matricaria chamomilla L. that experimental group 2 was treated by it, could not prevent increase of Superoxide Dismutase in Red Blood Cell and Malondialdehyde in plasma at the end of the study compared to its beginning. Conclusion: The results of this research indicate that M. chamomilla L. has good antioxidant activity and can contrive making natural antioxidant compounds to prevent diseases caused by oxidative stress.